Percutaneous vagus nerve stimulation modulates glia activity and rescues acute Aβ deposition in a mouse model of delirium superimposed on dementia. (1st February 2022) - Velagapudi, Ravikanth; Huffman, William J; Zhang, Xiaobei; Colton, Carol A; Terrando, Niccolo
Abstract: Background: Millions of Americans live with Alzheimer's disease (AD) and routinely require common surgical interventions, such as orthopedic surgery. However, these potentially life‐saving procedures often increase the risk for further cognitive complications, such as delirium, which in many cases associate with worse prognosis and even death. Currently, we do not have effective strategies to prevent postoperative neuroinflammation and treat delirium. Using an AD‐like mouse model (CVN‐AD) we established a translational paradigm to study delirium superimposed on dementia [1]. Method: Here we describe the effects of a minimally‐invasive ultrasound guided percutaneous approach to stimulate the vagus nerve (termed pVNS) [2] in CVN‐AD mice after orthopedic surgery. A 30‐minute stimulation at 10 Hz was performed in 12‐months‐old CVN‐AD mice before subjecting them to tibial fracture and repair. Result: Surgery induced a robust neuroinflammatory response in these mice, with evident morphological changes in microglia and astrocytes, as well as an acute deposition of Aβ plaques in the hippocampus compared to age‐matched controls. pVNS after surgery rescued morphological changes in microglia and astrocytes, as well as effectively reduced Aβ plaques deposition in the hippocampus at 24 hours. Notably, pVNS altered the autophagy‐lysosomal pathway by increasing TFEB and LAMP1 expression, which are key regulators of autophagy and lysosomal biogenesis. These changes were observed using Nanostring assay on hippocampal tissue combined with immunofluorescence staining. Conclusion: Overall, these data highlight a novel role for vagus nerve stimulation in regulating neuroimmune interactions and resolving inflammation in delirium superimposed on dementia